Quantifying Distribution of Flow Cytometric TCR-Vβ Usage with Economic Statistics - van der Geest, Kornelis S. M.; Abdulahad, Wayel H.; Horst, Gerda; Lorencetti, Pedro G.; Bijzet, Johan; Arends, Suzanne; van der Heiden, Marieke; Buisman, Anne-Marie; Kroesen, Bart-Jan; Brouwer, Elisabeth; Boots, Annemieke M. H. (PLOS ONE, 2015)
Measuring changes of the T cell receptor (TCR) repertoire is important to many fields of medicine. Flow cytometry is a popular technique to study the TCR repertoire, as it quickly provides insight into the TCR-Vβ usage among well-defined populations of T cells. However, the interpretation of the flow cytometric data remains difficult, and subtle TCR repertoire changes may go undetected. Here, we introduce a novel means for analyzing the flow cytometric data on TCR-Vβ usage. By applying economic statistics, we calculated the Gini-TCR skewing index from the flow cytometric TCR-Vβ analysis. The Gini-TCR skewing index, which is a direct measure of TCR-Vβ distribution among T cells, allowed us to track subtle changes of the TCR repertoire among distinct populations of T cells. Application of the Gini-TCR skewing index to the flow cytometric TCR-Vβ analysis will greatly help to gain better understanding of the TCR repertoire in health and disease.